Upregulating microRNA-373-3p promotes apoptosis and inhibits metastasis of hepatocellular carcinoma cells. Issue 1 (1st January 2022) - Li, Hongbin; Wang, Nan; Xu, Yuntian; Chang, Xiao; Ke, Jing; Yin, Jun
ABSTRACT: Hepatocellular carcinoma (HCC) is one of the most prevalent malignancies in the digestive system. Abnormal miR-373-3p and TFAP4 expressions are critical in many malignant tumors, but it is unclear whether they work in the context of HCC. qRT-PCR measured miR-373-3p expression in HCC tissues and adjacent normal tissues. Flow cytometry and Western blot analyzed cell apoptosis. EMT, Transwell, and wound healing assay examined HCC cell migration and EMT, respectively. Western blot determined the profile of TFAP4/PI3K/AKT. IHC detected Ki67, E-cadherin, and vimentin in the tumor tissues. Moreover, the downstream target of miR-373-3p was predicted using the database. Dual luciferase activity assay and RIP verified the binding correlation between TFAP4 and miR-373-3p. In HCC tissues and cell lines, miR-373-3p was downregulated, and its overexpression stepped up HCC cell apoptosis and suppressed migration and EMT. Furthermore, miR-373-3p overexpression elevated Bax and caspase 3 expressions and attenuated Bcl2's level. A xenograft tumor experiment in nude mice unveiled that miR-373-3p overexpression dampened tumor growth and proliferation. miR-373-3p cramped PI3K/AKT pathway activation. miR-373-3p negatively modulated TFAP4, and TFAP4 overexpression inverted miR-373-3p-mediated anti-tumor effects. Additionally, TFAP4 enhanced IGF1 expression, and promoted IGF1R-PI3K/AKT pathway activation. Collectively, miR-373-3p functions as an anti-tumor gene in HCC by inhibiting TFAP4/PI3K/AKT pathway.